Understanding hifdh and its effect on short-term memory recall performance: An experimental study on high school students in Saudi Arabia - Khan, Rabah (Institut Agama Islam Negeri Langsa, 2021)
Past literature suggests memorizing the Quran enhances one’s learning and overall memory performance. This study investigates the effect of hifdh on high school students’ short-term memory recall performance in Saudi Arabia. The research specifically aims to explore whether the ability to memorize Quran will affect the short-term memory of the individuals. One hundred high school students residing in Saudi Arabia, aged between 13-20 years, were divided into two groups of 50 students each. The first group consisted of huffadh students with 28 males and 21 females, while the non-huffadh group had 13 males and 36 females. All were given a word list recall task consisting of both English and Arabic word lists. They were asked to immediately recall words to the best they can at the end of every list. The analysis shows that the memory performance differed between the two groups. This finding suggests that hifdh has a significant effect on individuals’ short-term memory performance.